Characterization of Carboxylic Acid Reductases as Enzymes in the Toolbox for Synthetic Chemistry. Issue 6 (14th February 2017) - Finnigan, William; Thomas, Adam; Cromar, Holly; Gough, Ben; Snajdrova, Radka; Adams, Joseph P.; Littlechild, Jennifer A.; Harmer, Nicholas J.
Abstract: Carboxylic acid reductase enzymes (CARs) meet the demand in synthetic chemistry for a green and regiospecific route to aldehydes from their respective carboxylic acids. However, relatively few of these enzymes have been characterized. A sequence alignment with members of the ANL (Acyl‐CoA synthetase/ NRPS adenylation domain/Luciferase) superfamily of enzymes shed light on CAR functional dynamics. Four unstudied enzymes were selected by using a phylogenetic analysis of known and hypothetical CARs, and for the first time, a thorough biochemical characterization was performed. Kinetic analysis of these enzymes with various substrates shows that they have a broad but similar substrate specificity. Electron‐rich acids are favored, which suggests that the first step in the proposed reaction mechanism, attack by the carboxylate on the α‐phosphate of adenosine triphosphate (ATP), is the step that determines the substrate specificity and reaction kinetics. The effects of pH and temperature provide a clear operational window for the use of these CARs, whereas an investigation of product inhibition by NADP +, adenosine monophosphate, and pyrophosphate indicates that the binding of substrates at the adenylation domain is ordered with ATP binding first. This study consolidates CARs as important and exciting enzymes in the toolbox for sustainable chemistry and provides specifications for their use as a biocatalyst. Abstract : Driven in CARs : Carboxylic acid reductases (CARs) are enzymes that reduce such acids to aldehydes. Example CARs from across the phylogeny are characterized. Generally, CARs prefer electron‐rich substrates. Inhibition studies support an ordered binding of substrates in the first catalytic step.